A stakeholder assessment of the food fraud vulnerability of the South African meat sector : a case study of the Tshwane metropolitan area - Jordaan, Daniel du Plessis Scheepers (University of Pretoria, 2023)
Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2023.